PERANAN POLRI DALAM PENEGAKAN HUKUM PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) PADA MASA PANDEMI COVID-19 DI KOTA MEDAN - Pamilu Hamonangan; Triono Eddy (JURNAL DOKTRIN REVIEW, 2023)
The emergency PPKM policy was extended through PPKM policies with different levels in each region, in order to reduce the second wave of Covid-19 that has occurred since June 2021. The purpose of this research is to examine the supporting and inhibiting factors of the National Police in enforcing the PPKM law in Cities Medan, then to examine the application of sanctions against violators in implementing PPKM in Medan City, as well as to examine the role of the National Police as the Covid 19 task force in enforcing PPKM law in Medan City. The type of research in this research is normative research. The resultsof the research show that the supporting factors for the Indonesian National Police in serving the community are the involvement of the Government, the inhibiting factors are the limited budget for carrying out socialization, and the lack of human resources. Covid 19 in PPKM law enforcement in Medan City is maintaining security and publication during PPKM, enforcing the law for PPKM violations